JUVENILE XANTHOGRANULOMA: A CASE REPORT - Sara Pires da Silva; Catarina Viveiros; Rui Almeida; Marta Almeida Pereira; Rute Vaz; Alexandrina Portela (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To report a rate case of Juvenile xanthogranuloma in a newborn infant. Case description: We present the case of a 31-week preterm newborn with multiple skin lesions whose clinical, histological and immunohistochemical findings allowed the diagnosis of juvenile xanthogranuloma. Currently, the patient has nine months-old, and there is no aggravation of the skin lesions or evidence of extra-cutaneous involvement, particularly ophthalmic. Comments: Juvenile xanthogranuloma is a rare and benign condition, included in the vast group of non-Langerhans histiocytosis. It typically occurs in the pediatric age and may have a neonatal presentation. It affects predominantly the skin, in the form of papules or yellow and/or erythematous nodules and could be asymptomatic, multiple or solitary. Extra-cutaneous involvement, is more common in toddlers and when multiple lesions are present. The eye is the most affected site. We highlight this clinical case by its presentation in the neonatal period and in the form of multiple lesions, which bestows an increased risk of extra-cutaneous involvement, although this has not yet been verified.